KEMAMPUAN TEKNIK PERSONAL PADA EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI DENGAN PENDIDIKAN DAN PELATIHAN SEBAGAI PEMODERASI - Suartika, Kamajaya Adi; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
This study aimed to examine the effect of the ability of the technique  personal on the effective use of accounting information systems and to determining education and training in moderating the effect of  the ability of the technique of personal on the effective use of accounting information systems in KSP of Badung regency, research on 36 KSP Badung.  Sample selection is done by using purposive sampling method. Total respondent 108 people consisting of 1 KSP manager, 1 employee in the bookkeeping, and 1  employee in the cashier section of cooperatives in 36 KSP. Data collected through questionnaires. The analysis technique used in this study is Moderated Regression Analysis. The study found that the ability of the technique of personal positively effect on the effective use of accounting information systems, education and training strengthen the effect of the ability of the technique personal on the effective  use of accounting information systems
Keywords: ability of the technique, education training, effective use of SIA